Disseminated Cutaneous Histoplasmosis in Newly Diagnosed Hiv. Issue 1 (1st January 2016) - Soza, Gabriela M.; Patel, Mahir; Readinger, Allison; Ryan, Caitriona
Abstract : We present a woman with a widespread severe papulopustular eruption, fever, and fatigue of 5 weeks' duration. HIV infection was diagnosed, with an absolute CD4+ count of 3 cells/μL. The eruption was consistent with disseminated cutaneous histoplasmosis. The clinical manifestations and management of cutaneous histoplasmosis are reviewed.